The Effectiveness of Public Policy in the Management of Sustainable Marine Culinary Tourism - Syahrial, Syahrial; Mufti, Mohamad Irfan; Hakim, Abd.; Wijaya, Andry; Anjarsari, Hilda (SIGn Journal of Social Science, 2025)
The management of marine culinary tourism in Bulukumba Regency faces a fundamental paradox between the imperative of ecological conservation and the demands of tourism-based economic growth. The failure to balance these two aspects indicates a deeper problem than mere policy implementation. This research aims to critically analyze the effectiveness of public policy in managing sustainable marine culinary tourism. The analysis focuses on the root cause of this failure, identified as a governance deficit. Using a qualitative case study approach, data were collected through in-depth interviews with key stakeholders. These stakeholders included government elements, Micro, Small, and Medium Enterprise (MSME) actors, fishing communities, and environmental activists, supplemented by policy document analysis. The research findings reveal that the policy failure is rooted in a systemic governance deficit. It manifests in three forms: (1) a policy paradox that creates normative conflicts at the regulatory level; (2) an implementation gap where economic empowerment programs are partial, charitable in nature, and ecologically blind; and (3) the marginalization of local actors due to the dominance of an exclusive, top-down approach. It is concluded that the solution lies not in adding new regulations, but instead in a fundamental reconfiguration of the governance model. Therefore, a paradigm shift is recommended from hierarchical government to collaborative governance. This model places substantive public participation and community-based oversight at the center of achieving just, inclusive, and sustainable marine tourism.